Identification of Cocconeis neothumensis var. marina using a polyphasic approach including ultrastructure and gene annotation - Emanuele Somma; Maria Costantini; Chiara Pennesi; Nadia Ruocco; Olga De Castro; Antonio Terlizzi; Valerio Zupo (PLoS ONE, 2025)
Several microalgae, including marine diatoms, significantly contribute to the global primary production and play a vital role in the food webs of benthic and planktonic ecosystems. Diatoms of the genus Cocconeis frequently inhabit benthic substrates, including the leaves of seagrasses. They are seasonally dominant in the leaf epiphytic layer of the Mediterranean seagrass Posidonia oceanica L. Delile, and have been proposed as model organisms for chemical ecology studies. However, the genome of Cocconeis spp. has not been sequenced. Consequently, their low-level molecular identification is currently impossible, besides a few examples. To address this gap, a polyphasic identification of C. neothumensis has been employed, combining ultra-morphological data with DNA barcoding markers. A strain of diatoms was isolated from P. oceanica leaves. It has been cultured in the laboratory and examined under Scanning Electron Microscopy (SEM). The 18S ribosomal RNA gene (18S rRNA, nrDNA) and the ribulose 1,5-biphosphate carboxylase (rbcL, cpDNA) gene were analysed for DNA barcoding characterisation. Since ultra-morphology data unambiguously identified the isolated strain as C. neothumensis Krammer, 1991, the molecular sequences herein reported will facilitate its rapid and accurate identification. In addition, our comparative analyses will facilitate the evaluation of these molecular markers for identification of closely related benthic diatoms.